Proceedings of the 2016 Internet Measurement Conference 2016
DOI: 10.1145/2987443.2987486
|View full text |Cite
|
Sign up to set email alerts
|

Weak Keys Remain Widespread in Network Devices

Abstract: In 2012, two academic groups reported having computed the RSA private keys for 0.5% of HTTPS hosts on the internet, and traced the underlying issue to widespread random number generation failures on networked devices. The vulnerability was reported to dozens of vendors, several of whom responded with security advisories, and the Linux kernel was patched to fix a boottime entropy hole that contributed to the failures. In this paper, we measure the actions taken by vendors and end users over time in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…On the other hand, the guessing probability P g emerges naturally as the figure of merit by defining randomness as the unpredictability of a given distribution on a single use. This quantity tells us what is the best chance we have in predicting the outcome of a random (1), are followed by a LSTM layer, marked by (2), and two fully-connected layers, marked by (3). As a single input into RCNN, N (100) 13-bit integers are firstly encoded into one-hot vectors.…”
Section: F System Evaluationmentioning
confidence: 99%
“…On the other hand, the guessing probability P g emerges naturally as the figure of merit by defining randomness as the unpredictability of a given distribution on a single use. This quantity tells us what is the best chance we have in predicting the outcome of a random (1), are followed by a LSTM layer, marked by (2), and two fully-connected layers, marked by (3). As a single input into RCNN, N (100) 13-bit integers are firstly encoded into one-hot vectors.…”
Section: F System Evaluationmentioning
confidence: 99%
“…Reporting vulnerabilities through Computer Emergency Response Team (CERT) organizations appeared to be of limited utility. Hastings et al found even more disappointing results in their study of the response to disclosure of an RSA private key compromise for 0.5% of HTTPS-enabled Internet hosts [20]. In a different study on remediation of hijacked websites, Li et al reported that browser interstitials and search engine warnings correlated with faster remediation compared to private notification via WHOIS contact alone [29].…”
Section: Related Workmentioning
confidence: 99%
“…The output sequence of a DRNG is generated with a deterministic algorithm and a provided seed. Despite its good statistical characteristic, the DRNG is not suitable for information security applications, because the deterministic pattern of the DRNG may be identified by adversaries, which incurs malicious attacks and causes the destruction of security system, as in [ 2 , 3 , 4 , 5 ]. On the contrary, a NRNG produces the random sequence by using physical entropy sources, such as electrical noise [ 6 , 7 , 8 ], quantum fluctuations [ 9 , 10 , 11 , 12 ] and chaotic semiconductor lasers [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%